RANCANG BANGUN ALAT VOICE OPERATED EXCHANGE - Albert Mandagi (Jetri : Jurnal Ilmiah Teknik Elektro, 2014)
A Voice Operated Exchange (VOX) is a switch used in telecommunications that operates when a sound is detected and exceeds a certain threshold. It is often used to turn a transmitter or recorder on when a user speaks and off when a user stops speaking. A VOX is commonly used as part of video conference or telepresence equipment. It is also used in cellular phones to preserve battery life. Cellular phones, two-way radios, phone recorders and tape recorders often have VOX as an option. On intercom systems, a VOX on the main console is often used in a room with a speaker, which serves as both a speaker and a microphone to monitor sounds such as conversation. The device circuit consists of microphone and speaker, amplifier, voltage doubler, comparator, monostable multivibrator and relay. A VOX circuit takes only a voice or other sound to trigger it. It remains on as long as the sound remains above a certain volume or decibel level. The circuit automatically turns off when the volume drops below the minimum decibel level after a short delay. Keywords: microphone and speaker, voice, monostable multivibrator, relaysVoice Operated Exchange (VOX) merupakan sebuah saklar yang digunakan dalam telekomunikasi  yang bekerja pada saat terdeteksi suara yang  melebihi ambang tertentu. Hal ini sering digunakan untuk menghidupkan  pemancar atau perekam pada saat pengguna berbicara dan mematikan  ketika pengguna berhenti berbicara. Sebuah VOX umumnya digunakan sebagai bagian dari peralatan video conference atau  telepresence.  VOX  juga digunakan pada telepon selular untuk menghemat masa pakai baterai. Telepon selular, radio Citizen Band (CB), perekam telepon dan tape recorder sering memiliki VOX sebagai pelengkap.  Pada suatu sistem interkom, sebuah VOX pada console utama sering digunakan dalam sebuah ruangan dengan sebuah speaker, yang berfungsi baik sebagai speaker maupun  mikrofon untuk memonitor suara dalam  percakapan. Rangkaian VOX terdiri dari mikrofon dan speaker, penguat, pengganda tegangan, komparator, multivibrator monostabil dan relay. Rangkaian VOX hanya membutuhkan berbagai suara sebagai pemicu. Selama masih ada suara  di atas volume atau tingkat desibel tertentu, maka rangkaian akan bekerja. Rangkaian otomatis mati ketika volume suara turun di bawah tingkat desibel minimum setelah penundaan singkat . Kata kunci: mikrofon dan speaker, suara, multivibrator monostabil, relay